2021
DOI: 10.1017/ice.2021.495
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory virus coinfections with severe acute respiratory coronavirus virus 2 (SARS-CoV-2) continue to be rare one year into the coronavirus disease 2019 (COVID-19) pandemic in Alberta, Canada (June 2020–May 2021)

Abstract: To assess the burden of respiratory virus co-infections with SARS-CoV-2, this study reviewed 4,818 specimens positive for SARS-CoV-2 and tested using respiratory virus multiplex testing. Co-infections with SARS-CoV-2 were uncommon (2.8%), with rhinovirus/enterovirus as the most prevalent target (88.1%). Respiratory virus co-infections with SARS-CoV-2 remain low one-year into the pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Our subgroup analyses revealed that the rate of co‐infection was significantly higher in paediatric than in adult patients (9.39% vs. 3.51%, p ‐value = 0.03). These results are consistent with a recent study examining co‐infection rates for paediatric (10.0%) and adult (2.4%) patients 37 . The immature immune system in the youngest patients compared to adults and the greater interaction of children can explain the higher probability of co‐infection detection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our subgroup analyses revealed that the rate of co‐infection was significantly higher in paediatric than in adult patients (9.39% vs. 3.51%, p ‐value = 0.03). These results are consistent with a recent study examining co‐infection rates for paediatric (10.0%) and adult (2.4%) patients 37 . The immature immune system in the youngest patients compared to adults and the greater interaction of children can explain the higher probability of co‐infection detection.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with a recent study examining co‐infection rates for paediatric (10.0%) and adult (2.4%) patients. 37 The immature immune system in the youngest patients compared to adults and the greater interaction of children can explain the higher probability of co‐infection detection. Although meta‐analysis revealed a small increase in the co‐infection rate for female patients (11.1% in male vs. 15.5% in female, p ‐value = 0.12), the difference did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…The next two COVID-19 pandemic seasons (2020-2021 and 2021-2022) were dominated by the emergence of the more transmissible Delta and Omicron SARS-CoV-2 variants with immune escape capacity [4], while influenza had a negligible epidemiological and clinical impact if at all [16,17]. The circulation and morbidity burden of other respiratory viruses [e.g., RSV, human metapneumovirus (hMPV), adenoviruses, rhinoviruses] were also highly impacted by the COVID-19 pandemic, with wide temporal and geographic fluctuations [18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, simultaneous detection of multiple respiratory co-pathogens was performed using both multiplex real-time PCR and multiplex NGS analysis. Several studies have also used multiplex sequencing analysis to detect the presence of co-pathogens [ 13 , 31 , 60 , 61 , 62 ]. By applying target (t) NGS analysis, we identified SARS-CoV-2 variants found in mixed infections similar to those reported in other studies using this approach [ 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%